Effects of Sensor-Based Irrigation Shortage on Javanese Turmeric Yield and Curcumin Content During Generative Stage - Armelia Tanjung; Eka Nurhangga; Djatmiko Pinardi; Noorwitri Utami; Nur Alfi Saryanah; Ahmad Suhendra (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Javanese turmeric (Curcuma xanthorrhiza Roxb.) has a long harvest period and a critical generative phase for producing high-quality rhizomes. This characteristic of the plant, coupled with the uneven distribution of rainfall, floods in one area and droughts in another, limits surface irrigation. Therefore, this study aimed to determine the effect of irrigation shortage on the yield and curcumin content of Javanese turmeric during the generative phase. The experiment used a completely randomized design with four levels of field capacity (100%, 75%, 50%, and 25%), four treatment times (8, 7, 6, and 5 weeks before harvesting), with six replications, and plants harvested at 9 months. Irrigation was supplied to maintain field capacity conditions based on a visualization of calibrated soil moisture sensors on an Arduino 2560+ microcontroller. The results showed no significant difference in biomass production, indicated by fresh weight of roots and rhizomes, as well as dry weight of sliced rhizomes, across all levels of field capacity and treatment times. Further analysis using a clustering technique showed that the curcumin content at a field capacity of 25% initiated 5 weeks before harvesting, followed a distinct pattern. However, the control conditions tended to be higher than those of other treatments. This indicates that the lowest field capacity (25%) is sufficient to maintain biomass production during the generative phase. The curcumin concentration in the treatment group (75%, 50%, and 25% field capacity) was significantly lower than that in the control, as determined by DMRT analysis. Under the treatment conditions, the plants produced 0.47%, 0.46%, and 0.43%, respectively, while the control produced 0.56% curcumin. These results imply that the irrigation shortage had the same effect on biomass production as normal irrigation but reduced the curcumin content of Javanese turmeric plants during the generative phase.